Analysis Of Opportunities For Implementing The Amicus Curiae Concept As A Form Of Public Participation In The Judicial System In Indonesia - Thomas, Jerry; Liman, Vivaldi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
This research uses the normative juridical method, and it aims to determine the amicus curiae mechanism in the Indonesian legal system. The research results show that the implementation of amicus curiae in the judicial system in Indonesia still needs a common perspective among judges, where there are still judges who accept or reject this concept or do not even consider it at all. The concept of amicus curiae in the Indonesian legal system has yet to be a significant consideration because no explicit regulations accommodate it. Still, it is often stated that the position of amicus curiae is embodied through Article 5 of Act Number 48 of 2009 on Judicial Power, which mandates judges to explore, follow, and understand legal values and a sense of justice that lives in society. In line with these provisions, the judge has the authority to provide space and open up the broadest possible information and opinions from various groups who pay special attention to a case being examined.Â Judges using amicus curiae in their considerations, both from a philosophical, sociological, and juridical perspective, aim to prioritize legal certainty and provide justice with the participation of society. The research then provides a suggestion that the Supreme Court of the Republic of Indonesia can issue a Policy Circular or through a Decree of the Chief Justice of the Supreme Court regarding guidelines that judges can use to implement amicus curiae and how to assess the quality of information in amicus curiae.